Can Offering a Signing Bonus Motivate Effort? Experimental Evidence of the Moderating Effects of Labor Market Competition - Choi, Jongwoon (Willie) (The Accounting Review, 2014)
ABSTRACT Employers often rely on informal controls such as trust to motivate organizationally desirable behaviors from their workers by appealing to the latter's reciprocity. Notably, trust and reciprocity can promote a “gift exchange” between employers and workers. Using an experiment, I investigate whether labor market competition moderates the emergence of a gift exchange in labor markets in which signing bonus offers serve as a potential signal of trust and the duration of the employment relationship is endogenously determined. I find that offering a signing bonus more positively affects both workers' beliefs about the employer's trust in them and their effort when there is an excess supply of workers than when there is an excess demand for workers. I also find that the initial effects of signing bonuses may not persist over time. Additional analyses suggest that both employers' and workers' expectations may affect whether and how trust and reciprocity develop over time.